Serious adverse event rates and reoperation after arthroscopic shoulder surgery: population based cohort study. (6th July 2022) - Rees, Jonathan L; Craig, Richard; Nagra, Navraj; Baldwin, Mathew; Lane, Jennifer C E; Price, Andrew; Beard, David J; Abram, Simon; Judge, Andrew; Prieto-Alhambra, Daniel; Furniss, Dominic; Carr, Andrew J
Abstract: Objective: To provide clinicians and patients with accurate risk estimates of serious adverse events after common elective shoulder arthroscopic procedures, including reoperation within one year. Design: Population based cohort study. Setting: Hospital Episode Statistics for NHS England, including civil registration mortality data from the Office for National Statistics. Participants: 288 250 arthroscopic shoulder procedures performed in 261 248 patients aged ≥16 years between 1 April 2009 and 31 March 2017. Elective procedures were grouped into subacromial decompression, rotator cuff repair, acromioclavicular joint excision, glenohumeral stabilisation, and frozen shoulder release. Main outcome measures: The primary outcomes were rates of serious adverse events (mortality, pulmonary embolism, pneumonia, myocardial infarction, acute kidney injury, stroke, and urinary tract infection) requiring inpatient care within 90 days post-surgery. Secondary outcomes were specific adverse event rates at 90 days, and reoperations (including for deep infection) within one year. Results: The overall rate of complications within 90 days after arthroscopic shoulder surgery (including reoperation) was low at 1.2% (95% confidence interval 1.2% to 1.3%), with one in 81 patients at risk, and varied according to type of procedure, from 0.6% (0.5% to 0.8%) for glenohumeral stabilisation to 1.7% (1.5% to 1.8%) for frozen shoulder release. After adjustment for age, comorbidities, and sex, no effect of procedure type was observed. Pneumonia was the most common adverse event (0.3%, 0.3% to 0.4%), with one in 303 patients at risk. Pulmonary embolic events were rare, at 0.1% (0.1% to 0.1%), with one in 1428 patients at risk. At one year, the overall rate for reoperation was 3.8% (3.8% to 3.9%), with one in 26 patients at risk, ranging from 2.7% (2.5% to 3.0%) for glenohumeral stabilisation to 5.7% (5.4% to 6.1%) for frozen shoulder release. The overall rate of further surgery for deep infection was low, at 0.1% (0.1% to 0.1%), with one in 1111 patients at risk, but was higher after rotator cuff repair (0.2%, 0.2% to 0.2%), with one in 526 patients at risk. Over the study period the number of arthroscopic shoulder procedures increased, except for subacromial decompression, which decreased. Conclusions: The findings of this study suggest that risks of serious adverse events associated with common shoulder arthroscopy procedures are low. Nevertheless, serious complications do occur, and include the risk of reoperation in one in 26 patients within one year. Study registration: Clinical.Trials.gov NCT03573765 .